2013
DOI: 10.1111/nph.12528
|View full text |Cite
|
Sign up to set email alerts
|

Premature and ectopic anthocyanin formation by silencing of anthocyanidin reductase in strawberry (Fragaria × ananassa)

Abstract: Summary Strawberry (Fragaria × ananassa) is a fruit crop with a distinct biphasic flavonoid biosynthesis. Whereas, in the immature receptacle, high levels of proanthocyanidins accumulate, which are associated with herbivore deterrence and pathogen defense, the prominent color‐giving anthocyanins are primarily produced in ripe ‘fruits’ helping to attract herbivores for seed dispersal. Here, constitutive experimental down‐regulation of one branch of proanthocyanidin biosynthesis was performed. As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 39 publications
(54 reference statements)
2
49
1
Order By: Relevance
“…In strawberry, redirection of the proanthocyanidin pathway to anthocyanin was observed through down‐regulation of ANR leading to accumulation of anthocyanins, while down‐regulation of UPGT induced redirection of the anthocyanin pathway to the proanthocyanidin pathway (Fischer et al . ). The present transcriptomic analysis indicated that both ANR and LAR involved in the proanthocyanidin branch of the flavonoids did not differ significantly in expression between green and red calli, which suggests that proanthocyanidins might have no obvious effect on the biosynthesis of anthocyanins.…”
Section: Discussionmentioning
confidence: 97%
“…In strawberry, redirection of the proanthocyanidin pathway to anthocyanin was observed through down‐regulation of ANR leading to accumulation of anthocyanins, while down‐regulation of UPGT induced redirection of the anthocyanin pathway to the proanthocyanidin pathway (Fischer et al . ). The present transcriptomic analysis indicated that both ANR and LAR involved in the proanthocyanidin branch of the flavonoids did not differ significantly in expression between green and red calli, which suggests that proanthocyanidins might have no obvious effect on the biosynthesis of anthocyanins.…”
Section: Discussionmentioning
confidence: 97%
“…Plant transformation was performed using the Agrobacterium tumefaciens strain EHA105 complemented with the binary plasmid vector pK7GWIWG2D(II)_TFL1‐RNAi (Koskela et al ., ) as described by Fischer et al . (). Regenerated meristems were excised 9–12 weeks postinoculation.…”
Section: Methodsmentioning
confidence: 97%
“…The key structural genes for flavonoid biosynthesis encode essential biosynthetic enzymes. Expression of early biosynthetic genes (EBG) (Figure ), including phenylalanine ammonia‐lyase ( PAL ), cinnamate 4‐hydroxylase ( C4H ), 4‐coumarate:coenzyme A ligase ( 4CL ), chalcone synthase ( CHS ), chalcone isomerase ( CHI ), and late biosynthetic genes (LBG) (Figure ), including flavonol synthase ( FLS ) for the formation of flavonols, dihydroflavonol‐4‐reductase/flavanone‐4‐reductase ( DFR ), anthocyanidin synthase ( ANS ) and flavonol‐O‐glucosyltransferases ( UFGT ), is required for the formation of anthocyanins; and expression of leucoanthocyanidin reductase ( LAR ) and anthocyanidin reductase ( ANR ) is required for the formation of proanthocyanin precursors and proanthocyanins (Figure ; Fischer et al , ; Griesser et al , ).…”
Section: Introductionmentioning
confidence: 99%